Establishment of a genome map-based karyotype of Artemisia argyi and identification of a new octoploid - Li, Lina; Du, Pei; Liu, Dahui; Li, Xiangyang; La, Guixiao; Shi, Guixia; Dai, Dandan; Yang, Tiegang (Frontiers in Plant Science, 2025)
Artemisia argyi, an essential plant in traditional Chinese medicine, encounters significant challenges in the development of germplasm resources and cytological research. This study employed the A. argyi reference genome to develop 20 repetitive sequence oligonucleotide (oligo) probes, all of which produced clear signals on the chromosomes of the cultivar Qicun Xiang Ai (QCXA). These probes were configured into two probe cocktails (Multiplex #1 and Multiplex #2) that effectively generated chromosome signals under non-denaturing hybridization conditions through probe staining. By integrating probe staining with 45S rDNA fluorescence in situ hybridization (FISH) and electronic localization techniques, we established a genome map-based karyotype for QCXA that corresponded to its genomic sequence map. Utilizing this karyotype, we identified almost all chromosomes of the cultivars Wan Ai Ls-9 (WALs-9), Anguo Qi Ai (AGQA), and Anyang Bei Ai (AYBA) and investigated meiotic chromosome pairing behavior in WALs-9. These findings suggest that A. argyi may be a distinctive allotetraploid with a base chromosome number of 17. while AYBA (x = 8) appears to be a related species. Furthermore, a novel octoploid germplasm (APLs-9) is successfully generated and characterized through chromosomal doubling, demonstrating significantly enhanced moxa length and moxa content per leaf area - traits with substantial potential for improving both quality and yield. The developed octoploid and high-resolution karyotyping system are poised to significantly advance A. argyi breeding and production.